ANALISIS IDENTITAS KULTURAL DALAM PUISI “IBU INDONESIA” KARYA SUKMAWATI SOEKARNO PUTRI - Aryani, Elda; Yunengsih, Yuyu; Ismayani, Mekar (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Every verse in poetry must have a specific purpose to convey to its readers, there is no temple that has no meaning and message to convey. This study aims to analyze cultural identity in the poem "Ibu Indonesia" by Ibu Sukmawati Soekarno. The method used in this study uses the Qualitative Content Analysis method (Qualitative Content Analysis) this method is a research method that examines and discusses the contents of the text by giving an interpretation of the text that has been determined according to the purpose of the study. the reason the researchers chose this method was because this method could avoid the arbitrary interpretation of Indonesian mother poetry texts by sukmawati mother Soekarno putri, the results of this study showed that the poem contained elements of cultural identity including condes, veils, Indonesian mother's singing sounds and the call to prayer.